Subjective Age as a Moderator in the Reciprocal Effects Between Posttraumatic Stress Disorder Symptoms and Self-Rated Physical Functioning - Shrira, Amit; Palgi, Yuval; Hoffman, Yaakov; Avidor, Sharon; Bodner, Ehud; Ben-Ezra, Menachem; Bensimon, Moshe (Frontiers in Psychology, 2018)
It is now widely acknowledged that physical decline may increase among middle-aged and older adults who suffer from PTSD. Much less is known about the temporal sequencing of PTSD and physical decline relationship over time. While PTSD can lead to physical decline, physical decline may preserve or augment existing PTSD symptoms. Both problems can also mutually affect each other forming a vicious cycle. Additionally, it is important to address variables that can mitigate these longitudinal effects. Following the recovery capital framework, we consider how the existence, or lack of capital in the form of young age identity may affect the recovery process. Therefore, the current study aimed to examine the reciprocal effects of PTSD symptoms and self-rated physical functioning and further test whether one's subjective age moderates these effects. Using in-region random digit dialing, we collected a stratified sample of community-dwelling older adult residing in south Israel. Of that sample (N at T1=339), 132 older adults (age range=51-88, mean age=66.90, SD=9.14) were interviewed four months after the 2014 Israel-Gaza conflict (T2) and one year later (T3). Participants responded to PTSD symptoms scale, and reported their physical functioning and subjective age. PTSD symptoms and self-rated physical functioning were tested as both predictors and outcomes in a cross-lagged model. The moderating effect of subjective age was assessed by examining whether T2 variables interacted with subjective age in predicting T3 outcomes. Results showed that higher PTSD symptoms at T2 were associated with subsequent lower self-rated physical functioning at T3, yet self-rated physical functioning at T2 did not predict PTSD symptoms at T3, highlighting the PTSD-self-rated physical function direction. Moreover, subjective age moderated this latter association, so that this relationship was significant only for those who felt relatively older. In addition to clarifying the temporal sequencing of the PTSD-self-rated physical functioning association, the study further suggests that an older subjective age (i.e., lack of recovery capital) could render middle-aged and older adults more susceptible to physical decline following PTSD symptoms. We therefore propose to develop interventions aimed at coping with an older age identity and facilitating a younger age identity among traumatized older individuals.